1998
DOI: 10.1016/s0014-5793(98)00692-9
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of actin microfilaments by cytochalasin D leads to activation of p53

Abstract: Activation of p53 plays a central role in the cell's response to various stress signals. We investigated whether p53 is activated upon disruption of actin microfilaments, caused by cytochalasin D (CD). We show that treatment with CD leads to accumulation of p53 in the cells and activation of p53-dependent transcription. Treatment with CD led to arrest of G1-to-S transition in cells retaining wild-type p53, while cells with inactivated p53 showed partial rescue from it. CD also induces apoptosis in p53+/+, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 30 publications
5
54
0
1
Order By: Relevance
“…Others (Comer et al, 1998) have reported that p53 stimulates a-actin promoter activity, suggesting a role for p53 in cytoskeletal organization. At the protein level, indirect evidence for p53-actin interactions comes from the ®nding that actin ®lament disruption leads to p53 activation (Rubtsova et al, 1998). Our own data demonstrates a direct interaction between p53 and F-actin which is subject to regulation by calcium.…”
Section: Discussionmentioning
confidence: 76%
“…Others (Comer et al, 1998) have reported that p53 stimulates a-actin promoter activity, suggesting a role for p53 in cytoskeletal organization. At the protein level, indirect evidence for p53-actin interactions comes from the ®nding that actin ®lament disruption leads to p53 activation (Rubtsova et al, 1998). Our own data demonstrates a direct interaction between p53 and F-actin which is subject to regulation by calcium.…”
Section: Discussionmentioning
confidence: 76%
“…We propose that this theme can be enlarged to include the status of actin ®bres as well. In further support of the latter idea are the observations that disruption of actin by either heat or cytochalasin treatment (Rubtsova et al, 1998) also activates and stabilizes p53 (Klotzsche et al, 1998). In addition, it is noteworthy to list the proteins encoded by p53 regulated genes whose function is integral to the cytoskeletal architecture.…”
Section: Gip-17mentioning
confidence: 90%
“…Treatment with a number of drugs a ecting the integrity of the cytoskeleton, either at the level of microtubules (vinblastine, nocodazol, vincristine, colchicine and taxol Tishler et al (1995)), or at the level of actin ®bres (cytochalasin; Rubtsova et al (1998)), and heat shock (Li et al, 1999)), results in a stabilized and activated p53. This type of observation prompted Wahl and colleagues in a recent review to hypothesize that p53 or a protein(s) upstream of p53 senses microtubule disarray (Jimenez et al, 1999).…”
Section: Gip-17mentioning
confidence: 99%
“…Cytochalasin drugs that impair actin polymerization stop the cell cycle [3][4][5]. This effect could be due to a requirement for the actin cytoskeleton to progress through mitosis, for example during constriction of the cleavage furrow, which is mediated by myosin motors walking on actin filaments.…”
mentioning
confidence: 99%
“…This cell cycle block, however, was observed even when very low doses of cytochalasin, which had no visible effects on cleavage or adhesion, were used [5]. The cytochalasin-induced block occurred in G1, and this G1 block was alleviated when p53 or Rb tumor suppressors were inactivated [4,5] ( Table 1). Again such a rescue suggested a specific signaling pathway from the actin structure to cell cycle machineries rather than a general requirement for actin.…”
mentioning
confidence: 99%